Generation and characterization of specific chicken egg yolk immunoglobulins against nucleocapsid protein of porcine reproductive and respiratory syndrome virus - WAN Xiao-yuan; HU Hong-xia; CHEN Ning; ZOU Xiao-ting; LI Xiao-liang (浙江大学学报. 农业与生命科学版)
The gene encoding nucleocapsid protein (N) of porcine reproductive and respiratory syndrome virus (PRRSV) was cloned into prokaryotic expression vector pET-30a (+), and the recombinant plasmid was transformed into Escherichia coli BL21(DE3) pLysS for expression of the fusion protein 6 × His-N. The results showed that the yield of fusion protein 6 × His-N in BL21 was 60.2 mg·L-1. The purified fusion protein 6 × His-N was emulsified with an equal volume of Freund's complete adjuvant and used as antigen to immunize Hylan hen for three times to produce chicken egg yolk immunoglobulins (IgY) against N protein. ELISA results revealed that the specific antibody was firstly detected in the egg yolk at day 36 post-immunization (P/N=2.44). The peak was reached at day 83 post-immunization (P/N=5.63) and still had P/N=2.29 by a 1∶640 dilution of yolk. SDS-PAGE and Western blot analysis showed that the purified egg yolks possessed high purity and good immunoreactivity. These results indicate that specific IgY antibodies can be easily produced by immunization of hens with the recombinant fusion protein 6 × His-N and is a novel alternative antibody source as a diagnostic kit reagent of PRRSV.